Walking convenience in urban community in promoting "Green Neighbourhood" / Hafazah Abdul Karim and Puziah Ahmad - Abdul Karim, Hafazah; Ahmad, Puziah (Research Management Institute (RMI), 2014)
Research background: The rapid growths of the cities in terms of economic and social development are the reasons that lead to major development problems in most of the country around the world. Many approached have been made to Malaysia in encounter the development problem such as green neighbourhood concept. However, the concept still lacking in certain areas especially for encourage people to walk conveniently to reach the community facilities in the neighbourhood area. In additional, there is the need to evaluate the community facilities planning guidelines by considering walking convenience in neighbourhood area. This research intends to fill these two gaps in Malaysian community facilities planning study to encourage more sustainable environment for all. Other than that, this research also supports to achieve the objective of Putrajaya Green City Plan 2025. Objectives: This research outlines two main objectives which are; (1) to determine the walking behaviour in urban community towards creating green neighbourhood and (2) to evaluate the planning of community facilities by considering walking convenience in neighbourhood area. Methods: This research is the mixed method research of two types of survey which are semi structured interview and questionnaire survey. Semi structure interview measures the professional opinion while, questionnaire survey measures perception of residents on walking behaviour and walking conveniences in the neighbourhood area. Case studies: The research was conducted in Putrajaya because Putrajaya used the garden city approach and also to encounter Putrajaya walkability problems. Two Precincts of different housing characteristic but similar community facilities planning characteristic were chosen as the case studies, Precinct 8 and Precinct 9 neighbourhood area. Findings and conclusion: Findings show that walking convenience does significantly influence the level of walkability in Putrajaya neighbourhood area. Moreover, the findings also indicate that residents in high density residential area (Precinct 9) tend to walk more compare to residents with low density residential area (Precinct 8).